Comparison of DNA isolation of Candida albicans with filter-based kit and cooling methods - Muhammad Thoriq Aulia Khamim; Qurrohman, Muhammad Taufiq (Universitas 'Aisyiyah Yogyakarta, 2023)
Candidiasis is a disease caused by the fungus Candida sp., which can infect the skin, hair, mucous membranes, and internal organs. Laboratory diagnosis of Candida albicans can be done molecularly with the aim of identifying fungal DNA through DNA isolation as an initial stage. This study used an experimental research design used to compare two DNA isolation methods, namely filter-based kits and cooling. DNA purity is assessed by measuring absorbance at 260 nm and 280 nm. Qualitative evaluation is carried out through visualization of DNA bands in electrophoresis. After conducting five DNA re-isolation experiments for both filter-based kit and cooling methods, the highest DNA concentrations were observed in samples isolated using filter-based kits, with a result of 6.465 μg/μL. In addition, an adequate level of purity is achieved with this method. In addition, thicker and lighter bands of DNA are observed, which can be attributed to the use of the enzyme Lyticase and other chemicals. The variability of isolation results can be affected by several factors, including extraction speed, sample type, extraction method, and environmental conditions. Technical errors during measurements can also affect the amount of DNA. In comparison, DNA isolation using filter-based kits for Candida albicans resulted in superior quantity and quality of DNA compared to cooling methods.